INVESTMENT AND FINANCING ANALYSIS OF AUTOMOTIVE INDUSTRY OF CHINA - Azam, S.M. Ferdous; Yusoff, Siti Khalidah Mohd (International Journal of Psychosocial Rehabilitation, 2020)
With rapidly growth in economy, the China’s society is changing. Automobile became necessary consumption of the society. Automotive industry of China which has been expected as pillar industry in 2010 has experienced the impacts of changing of general environment and rapid growth, especially in 2002 and 2003; the annual growth rates were 37.1% and 35.1%. The industry is expected to maintain stable and high growth in the following couple years for the percentage in ownerships of cars in China is relative low. Currently, huge capitals crowd into the automotive industry of China and the China’s automobile industry is facing opportunities and challengers, the industry in China need adjust itself to adapt the changing of general environment and to achieve new development in the booming economy. As a consequence, there is necessary to study investment and financing issues which have become two critical issues for the industry.